Comparative efficacy of intravenous dexmedetomidine, clonidine, and tramadol in postanesthesia shivering - Shikha Sahi; Mirley Rupinder Singh; Sunil Katyal (Journal of Anaesthesiology Clinical Pharmacology, 2016)
Background and Aims: Postanesthesia shivering continues to be a major challenge in the perioperative care. We compared the efficacy of tramadol, clonidine, and dexmedetomidine in preventing postoperative shivering and its potential adverse effects in patients undergoing laparoscopic cholecystectomy under general anesthesia. Material and Methods: One hundred and twenty American Society of Anesthesiologists I and II patients scheduled for elective laparoscopic cholecystectomy under general anesthesia were divided into four equal groups. Group 1 received clonidine 2 μg/kg, Group 2 received tramadol 1 mg/kg, Group 3 received dexmedetomidine 1 mcg/kg all intravenous diluted in NS to 5 ml, and Group 4 received NS intravenous 5 ml. Parameters analysed included postoperative blood pressure (BP), pulse rate, respiratory rate (RR), arterial saturation, and tympanic membrane temperature. Patients were observed for shivering episodes, sedation, pain, respiratory depression, nausea, and vomiting. Analysis of variance, Tukey′s post-hoc comparison, Chi-square test and Bonferroni post-hoc comparison test were performed using SPSS (Statistical analysis by Statistical Package of Social Sciences of Microsoft Windows) Statistics (version 16.0). Results: The incidence of shivering was 10, 3.3, 13.3 and 40% in Groups 1, 2, 3, and 4 respectively. Patients who were given tramadol had significantly less shivering than patients in clonidine and dexmedetomidine groups (P < 0.01). Conclusion: All the three drugs were effective in preventing postoperative shivering. However, tramadol has been found to be more efficacious in preventing postoperative shivering.